Use of english fairy tales to teach listening comprehension skills among second grade students at República de Francia Elementary School, David, Chiriquí - Serrano, Isamar (UDELAS, 2013)
Literature plays an important role in our life. Fairy tales as a part of the children's literature coud be a valuable source for teaching listening and comprehension english in the foreing language. Fairy tales might be considered one of the possible supplementary teaching materials for english language learners.